Muslim women's experiences of maternity services in the UK: qualitative systematic review and thematic synthesis - Tasneema Firdous; Zoe Darwin; Shaima M. Hassan (BMC, 2020)
Abstract Background This review aimed to identify and synthesise evidence of Muslim women's experiences of maternity services in the UK. A systematic review and thematic synthesis of qualitative evidence, unrestricted by type of publication was conducted. Muslim women who had accessed maternity services in the UK, regardless of obstetric or medical history were included. Method Databases were searched from 2001 to 2019 and screened for inclusion using pre-determined criteria. The Critical Appraisal Skills Programme Qualitative Research Checklist was used to assess study quality and findings were synthesised using thematic synthesis, as described by Thomas and Harden. Results Six studies were included. The following five themes were identified: Islamic practices and Individualised care; Talk, Teach and Translate; Injustice, Inequity and Intolerance; If Allah wills; and, 'It's not all that bad'. Synthesis highlighted the significance of Islam in shaping many of the women's decision-making relating to antenatal screening and medication, which was contrasted with healthcare professionals' limited awareness of the importance of Islam for motherhood. The majority of women experienced poor maternity care which at times indicated stereotypical and discriminatory behaviour. Conclusions Education for healthcare professionals is warranted, to enhance the quality and cultural competency in providing appropriate care that acknowledges and meets Muslim women's needs.